2014
DOI: 10.1186/s12934-014-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional recombinant protein is present in the pre-induction phases of Pichia pastoris cultures when grown in bioreactors, but not shake-flasks

Abstract: BackgroundPichia pastoris is a widely-used host for recombinant protein production; expression is typically driven by methanol-inducible alcohol oxidase (AOX) promoters. Recently this system has become an important source of recombinant G protein-coupled receptors (GPCRs) for structural biology and drug discovery. The influence of diverse culture parameters (such as pH, dissolved oxygen concentration, medium composition, antifoam concentration and culture temperature) on productivity has been investigated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…4d). The AOX1 promoter is not known to have leaky expression when grown in shake flasks (Aw and Polizzi 2016), even though this is not the case for bioreactors (Bawa et al 2014). Therefore, this implies that there may be other stresses on α2, M1 and M2, such as the onset of starvation.…”
Section: Resultsmentioning
confidence: 99%
“…4d). The AOX1 promoter is not known to have leaky expression when grown in shake flasks (Aw and Polizzi 2016), even though this is not the case for bioreactors (Bawa et al 2014). Therefore, this implies that there may be other stresses on α2, M1 and M2, such as the onset of starvation.…”
Section: Resultsmentioning
confidence: 99%
“…This observation suggests that high recombinant protein yields in methanol-grown cells are due not just to promoter strength, but also to the global response of P. pastoris to growth on methanol [25]. However, P AOX1 -driven expression is leaky; the recent characterization of pre-induction expression under the control of P AOX1 [26] indicates that the uncoupling of growth and protein synthesis in P. pastoris cells has not yet been achieved. The response of a series of inducible S. cerevisiae promoters to different carbon sources has also been studied [22]; this type of careful analysis of promoter expression patterns now opens up opportunities for dynamic regulation of recombinant protein production in S. cerevisiae.…”
Section: The Promoter -Constitutive or Inducible?mentioning
confidence: 87%
“…We previously demonstrated the major impact of the induction regime on the yield of secreted GFP from P. pastoris cultures, showing the importance of matching the composition of the methanol feedstock to the metabolic activity of the cells [86]. P AOX1 is induced on methanol; however, when glucose (which has been shown to repress AOX1 expression) was the pre-induction carbon source, the adenosine A 2A receptor and GFP were still produced in the pre-induction phases in bioreactor cultures [26]. This study also reveals that a range of recombinant membrane proteins can be detected in the pre-induction phases of P. pastoris cultures when grown in bioreactors, but not shake-flasks.…”
Section: Induction Conditionsmentioning
confidence: 96%
See 1 more Smart Citation
“…The AOX1 promoter is repressed in the presence of glucose or glycerol but strongly upregulated in the presence of methanol, making it a relatively tightly controlled expression system. However, recent research has identified protein expression occurring during the pre-induction phase in cultures grown in bioreactors but not in shaker flasks indicating that the promoter is leaky under certain conditions [6].…”
Section: Introductionmentioning
confidence: 99%